Contributions of Animal Models to the Mechanisms and Therapies of Transthyretin Amyloidosis - Ibrahim, Ridwan Babatunde; Liu, Yo-Tsen; Yeh, Ssu-Yu; Tsai, Jin-Wu (Frontiers in Physiology, 2019)
Transthyretin amyloidosis (ATTR amyloidosis) is a fatal systemic disease caused by amyloid deposits of misfolded transthyretin, leading to familial amyloid polyneuropathy and/or cardiomyopathy, or a rare oculoleptomeningeal amyloidosis. A good model system that mimic the disease phenotype is crucial for the development of drugs and treatments for this devastating degenerative disorder. The present models using fruit flies, worms, rodents, nonhuman primates and induced pluripotent stem cells (iPSCs) have helped researchers understand important disease-related mechanisms and test potential therapeutic options. However, the challenge of creating an ideal model still looms, for these models did not recapitulates all symptoms, particularly neurological presentation, of ATTR amyloidosis. Recently, knock-in techniques was used to generate two humanized ATTR mouse models, leading to amyloid deposition in the nerves and neuropathic manifestation in these models. This review gives a recent update on the milestone, progress and challenges in developing different models for ATTR amyloidosis research.